Galerie Haas AG Zürich - Art Cologne. - Galerie Haas AG, Zürich (Köln Zürich : Art Cologne; Galerie Haas AG, 2007)
=oggi e adesso (d.i. Christina Feuser) ; Baselitz, Georg ; Copley, William ; Cragg, Tony (Anthony) ; Gartner, Marianna ; Bohnhoff, Stefan ; Brandl, Herbert ; Jordan, Richard ; Kirkeby, Per ; Klapheck, Konrad ; Kluge, Gustav ; Kuehn, Gary ; Meese, Jonathan ; Ofili, Chris ; Ottersbach, Heribert C. ; Rainer, Arnulf ; Rattray, Diane ; Soutter, Louis ; Vásquez de la Horra, Sandra ; Warhol, Andy ; Wirths, René
Duits
Exhibition. Art Cologne 2007. Art Cologne Köln. 2007-04-18. 2007-04-22
boek